PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN VIDEO INTERAKTIF DALAM MENINGKATKAN KESADARAN SEJARAH SISWA KELAS X IPA DI SMA NEGERI 3 PONTIANAK - Merianti Merianti; Maria Ulfah; Astrini Eka Putri (Universitas Tanjungpura, 2022)
The study aims to find out the class X Science awareness ofstudents at school looked after the land of 3 Pontianak. Theresearch method used was a quantitative method with anaerialized interrogation jeris. The research site was at statehigh school 3 Potianak. The data decoding technique that’sdone in research is observation, indirect communication, anddocumentation, while the tools used in researcg wereobservation guides, questionnaire, and documentary studies.The data analysis techniques used in the study are analysis ofdescriptive data using the likert scale, validity test, religioustest, normality test, homophobic test and linearial test andsimple linear regressions test, paired sample t-test test andeffect size. The research data source is the X class the x’s arehistory awareness sheets distributed in experiment and controlclasses. The results of this study show increased student historyawareness from before media use 55.56% and after media useincreased to 67.5%. and based of the testing of t-test samples,the impact of the interaktif media use on which t-count > t-tablefor 3,857 > 1,725 with dk 21-1=20 and a significant degree (a)=5% and the level of impact the used of interative videolearning media is 84% of the higher levels in cohen’s tables.